2018
DOI: 10.1088/1674-1056/27/8/088202
|View full text |Cite
|
Sign up to set email alerts
|

Improved electrochemical performances of high voltage LiCoO2 with tungsten doping

Abstract: The effects of tungsten W doping and coating on the electrochemical performance of LiCoO 2 cathode are comparatively studied in this work. The amount of modification component is as low as 0.1 wt% and 0.3 wt% respectively. After 100 cycles between 3.0 V-4.6 V, 0.1 wt% W doping provides an optimized capacity retention of 72.3%. However, W coating deteriorates battery performance with capacity retention of 47.8%, even lower than bare LiCoO 2 of 55.7%. These different electrochemical performances can be attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Element doping can change the crystal structures of cathode materials at the atomic level, thereby affecting their physical and chemical properties, such as the band gap, lattice constant, defect concentration, and charge distribution. To enhance the structure and cycle stability, a variety of element dopants have been introduced in LCO, such as Ni, Mg, Al, Cu, and W. , Kim et al introduced Mg into LCO by a high-temperature solid-state method, which could enhance the electrical conductivities of LCO to improve the diffusion of Li + and electrochemical performance . Recently, Yoon et al demonstrated that the Ni doping in LCO (LCNO) had a smaller effect on the bulk than the surface .…”
Section: Modification Strategies Of “Single-crystal” Cathodesmentioning
confidence: 99%
“…Element doping can change the crystal structures of cathode materials at the atomic level, thereby affecting their physical and chemical properties, such as the band gap, lattice constant, defect concentration, and charge distribution. To enhance the structure and cycle stability, a variety of element dopants have been introduced in LCO, such as Ni, Mg, Al, Cu, and W. , Kim et al introduced Mg into LCO by a high-temperature solid-state method, which could enhance the electrical conductivities of LCO to improve the diffusion of Li + and electrochemical performance . Recently, Yoon et al demonstrated that the Ni doping in LCO (LCNO) had a smaller effect on the bulk than the surface .…”
Section: Modification Strategies Of “Single-crystal” Cathodesmentioning
confidence: 99%
“…6, there were only a pair of main charge-discharge reaction peaks, corresponding to the transition from hexagonal phase to monoclinic phase, which meant that the doping of manganese and chromium suppresses the other phase transitions generated by the cathode material at high voltage. Nevertheless, a larger number of charges may lead to a larger interlayer spacing, which would distort the phase structure of the material, [96][97][98][99] so it was necessary to control the doping amount of manganese and chromium. 81 Copyright 2019, Advanced Functional Materials.…”
Section: Trivalent-metal-cation Dopingmentioning
confidence: 99%
“…Over the decades, various strategies have been proposed to stabilize the cycling performance of LCO at high voltage, such as single element Mg, 28,29 Sb, 30 Al, 31 W, 32 Ti, 33 Mn, 34 Ni, 35 or Zr 36 doping and surface Al 2 O 3 , 37,38 ZrO 2 , 39,40 MgF 2 , 41 CoTiO 3 , 42 Li 2 CO 3 , 43 Al-doped ZnO, 44 or Li 1.2 Mn 0.6 Ni 0.2 O 2 45 coating. Elemental doping has been shown to modify the lattice at the atomic scale to tune the fundamental physicochemical properties of materials.…”
Section: Introductionmentioning
confidence: 99%